Vegetation soil relationships as aids to soil survey in semi-arid areas - Zhou, Neil Mandinyenya (University of Zimbabwe, 2017)
The hypothesis that vegetation and woody species indicate soil type and land potential is very common in Zimbabwe and other similar countries. Research in vegetation – soil relationships to test this hypothesis in Zimbabwe is very limited. This thesis explores relationships between vegetation and soils along granite catenas found in semi arid areas of Zimbabwe. The main objective was to establish the relationship between the two, so that they could be used as a land quality indicators for increased agricultural production in these areas. The study was conducted on granite in Mushandike Wildlife Sanctuary, Makoholi Research Station and Gutu Soti-Source Resettlement, all in Masvingo Province within agro ecological region III and IV and in Maruta village found in Wedza Communal land of Mashonaland East Province also in agro ecological region III. Satellite image and air photo interpretations, vegetation classification and mapping together with vegetation measurements and soil profile assessments were used as data collection methods. Laboratory analyses of soils were done using standard procedures followed by AREX. Vegetation identification and measurements were done during the rainy season between November and April 1999. Plant species and soils data collected were prepared in appropriate formats for statistical analyses with the aid of SPSS statistical package. Vegetation community data were analysed using multivariate ordination techniques that include Cluster analysis, Detrended Correspondence Analysis (DCA) and Canonical Correspondence Analysis (CCA).